ANALYSIS OF THE PROFESSIONAL QUALIFICATIONS AND COMPETENCIES OF TEACHER EDUCATORS AND SUBJECT TEACHERS OF EDUCATION - Zahoor, Fatima; Jumani, N. B.; Nawaz, Allah (International Journal of Psychosocial Rehabilitation, 2020)
Many researches had stated that world class educational system from pre-school to postgraduate levels could convert the raw talents of its people into productive asset. A world class education system is not possible without world class teachers, most importantly at the foundational level, who instruct, inform and inspire their students to quality learning and scholarship. The present study analyzed the professional qualifications and competencies of teacher educators and subject teachers of education. The respondents were categorized into three groups in order to measure their competencies and professional qualification. These were Heads / Principals, Teacher Educators and Subject Teachers of Education and their students. Questionnaires were used as instruments for data collection. T-test and Percentage were applied for the purpose of analysis. The data analysis states that subject teachers of education were more efficient as compared to teacher educators. At the end, the researcher concluded that majority of the teacher educators and subject teachers of education did not have professional qualification and they had MA education as an academic degree. The results of the study concluded that subject teachers of education were efficient and competent as compared to teacher educators. It is suggested to the policy makers and planers that they may develop separate criteria for the selection of teacher educators and subject teachers of education i.e. level of qualification, experience, professional qualification etc.